Attribute Discrimination Index-Based Method to Balance Attribute Coverage for Short-Length Cognitive Diagnostic Computerized Adaptive Testing - Wang, Yutong; Sun, Xiaojian; Chong, Weifeng; Xin, Tao (Frontiers in Psychology, 2020)
We propose a new method that balances attribute coverage for short-length cognitive diagnostic computerized adaptive testing (CD-CAT). The new method uses the attribute discrimination index (ADI-based method) instead of the number of items that measure each attribute (MGDI-based method) to balance the attribute coverage. Therefore, the information that each attribute provides can be captured. The purpose of the simulation study was to evaluate the performance of the new method and the results showed that: (a) Compared with uncontrolled attribute balance coverage method, the new method produced a higher mastery pattern correct classification rate (PCCR) and attribute correct classification rate (ACCR) with both the posterior weighted Kullback–Leibler (PWKL) and the modified posterior weighted Kullback–Leibler (MPWKL) item selection method. (b) Equalization of ACCR (E-ACCR) based on the ADI-based method leads to better results, followed by the MGDI-based method. The uncontrolled method leads to the worst results regardless of item selection methods. (c) Both ADI-based and MGDI-based methods produced acceptable examinee qualification rates, regardless of item selection methods, while it was relatively low for uncontrolled condition.